Strategi Pengembangan Usaha Peternakan Sapi Perah Rakyat di Kabupaten Boyolali - U. Barokah (Universitas Sebelas Maret (UNS), 2009)
The aim of this research was to study development strategy of effort ranch dairy cattle farmer. Basic method used in this research was descriptive. Determination of research area was purposive that was Boyolali Regency with subdistrict Musuk, and than taken one village is Sukorejo. Farmer taken as sample in this research are farmer have adult dairy cattle. The respondents were tahken by simple random sampling resulting 40 dairy cattle farmers. Development strategy of ranch of dairy cattle farmer implementation with improving management by a). improving business scale from farmer by exploiting governmental role, KUD, BRI by exploiting given programs, b) combining the feed so that get standard minimum cost and obtained quantity and quality fresh milk, c) doing the pure artificial insemination or embryo transfer from dairy cattle FH. Key words : Development strategy, animal agriculture, dairy cattle